Legality of Using Forex Trading Robot Applications in Commodity Futures Trading - Primadigantari, Anindya; Bagiastra, Nyoman (Riviera Publishing, 2022)
The purpose of this writing is used to analyze and understand the use of the Trading Robot Application in Futures Trading assets against a norm that is already in force in Indonesia with several phenomena that occur as a result of the use of a forex transaction trading robot application that is misused to commit crimes. The research method used in this paper is normative law which includes the statue approach, the historical approach and the sociological approach. The results of the study that the use of the Trading Robot Application has not been regulated in Law Number 10 of 2011 concerning Amendments to Law Number 32 of 1997 concerning Commodity Futures Trading and is an act that does not have a permit so that it can be subject to criminal sanctions. This creates a legal vacuum that can lead to uncertainty in the disharmonization of laws and regulations, especially in futures trading. Thus, it is necessary to update the law by aligning technological advances by covering aspects of legality, specifications, qualifications of trading robots, and the concept of illegal is an administrative violation as an effort to ensure legal certainty.